Calculation and Analysis of Mean Glandular Dose During a Mammogram - Khalid, Dastan (Sulaimani Journal for Pure and Applied Sciences, 2014)
Mammographic density is the difference in appearance of glandular to fatty tissue in a mammogram. Investigation in doses delivered in mammography is carried out. The Mean Glandular Dose (MGD) is calculated and compared to the standard values. The results show the value of MGD is comparable to some of the references, however there are very large variations in MGD and mAs with respect to specific Compressed Breast Thickness and percent glandularity. The results suggest a lack of understanding of radiation uses and the risks that are involved in x-ray induced breast cancer in Sulaimani hospitals especially the Mammography Centre.
Keywords: Mean Glandular Dose MGD; Mammography; Radiation Dose in Mammograhy